2005
DOI: 10.1097/01.ede.0000165821.90114.7f
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Ozone and Daily Mortality

Abstract: Overall, the results suggest short-term associations between ozone and daily mortality in the majority of the cities, although the estimates appear to be heterogeneous across cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(245 citation statements)
references
References 72 publications
12
228
3
2
Order By: Relevance
“…Although health impacts of ozone have been less investigated than of PM, existing studies in Europe and beyond (e.g. Mudway and Kelly, 2000;Gryparis et al, 2004;Bell et al, 2005Bell et al, , 2006Ito et al, 2005;Levy et al, 2005) show convincing, though small, positive associations between daily mortality and ozone levels, independent of the effects of PM (see Fig. 11).…”
Section: Muezzinoglu Et Al 2001mentioning
confidence: 96%
“…Although health impacts of ozone have been less investigated than of PM, existing studies in Europe and beyond (e.g. Mudway and Kelly, 2000;Gryparis et al, 2004;Bell et al, 2005Bell et al, , 2006Ito et al, 2005;Levy et al, 2005) show convincing, though small, positive associations between daily mortality and ozone levels, independent of the effects of PM (see Fig. 11).…”
Section: Muezzinoglu Et Al 2001mentioning
confidence: 96%
“…Risk estimates on ozone related mortality are higher in the warmer season. Temperature plays a significant role in the magnitude of the coefficients [30,31,32]. A meta-analysis on 95 US urban communities studies showed that a 20 lg/m increase in 1 h maximum ozone was associated with a 0.39% increase (95% CI 0.26-0.51) in all-cause mortality.…”
Section: Omentioning
confidence: 99%
“…A series of meta-analyses and evaluation of geographic and seasonal O 3 gas-related risk has provided evidence for the association between O 3 gas and mortality (15)(16)(17)(18)(19). As O 3 inhalation is accompanied by dangerous side-effects and since O 3 is a gas, its benefits are limited.…”
Section: Introductionmentioning
confidence: 99%